(untitled) (Clinics, 2021)
OBJECTIVES: To determine the role of the RBP4/PiC/SIRT3 signaling pathway in the opening of the mitochondria permeability transition pore (mPTP) in offspring rats with hypothyroidism during pregnancy. METHODS: Sixty Sprague-Dawley (SD) rats were employed in this study. Pregnancy was deemed successful when a sperm was found in the uterus. After one week of pregnancy, offspring rats were divided into the following groups: overall hypothyroidism group (OH group), subclinical hypothyroidism group (SCH group), and normal control group (CON group). The establishment of the hypothyroidism model was confirmed when the serum thyroid stimulating hormone (TSH) levels were higher than normal value and TT4 level was within the normal range. The renal mitochondria of offspring rats were extracted on the 14th postnatal day (P14) and 35th postnatal day (P35). RESULTS: At P14, no significant differences in the degree of mPTP opening and expression of phosphoric acid carrier vector (PiC) were detected between the rats in the OH group and the SCH group. However, the expression level of silent mating-type information regulation 3 homolog (SIRT3) was markedly reduced. Retinol-binding protein 4 (RBP4) expression increased in the rats from the OH group, relative to that in those from the SCH group. At P35, the degree of mPTP opening and the expression levels of PiC and RBP4 in the OH group were higher than those in the SCH group. However, SIRT3 expression in the OH group was lower than that observed in the SCH group. CONCLUSION: RBP4 plays an important role in early renal mitochondrial damage and renal impairment in rats suffering from hypothyroidism during pregnancy. The RBP4/PiC/SIRT3 pathway is thus involved in the opening of the renal mPTP in offspring rats with hyperthyroidism.